Initial Clinical Experience with Dynamic C-arm CT Perfusion Acquisitions - Yamazaki, Riki; Takaishi, Atsushi; Itokawa, Hiroshi (Nippon Hōshasen Gijutsu Gakkai zasshi, 2020)
Dynamic C-arm computed tomography perfusion (C-arm CTP) is a newly developed application that can provide cerebral perfusion images in the angio suite, similar to conventional multi-detector CTP in a diagnostic room. We introduce the workflow of C-arm CTP acquisition and our initial experience in a clinical setting.PURPOSEDynamic C-arm computed tomography perfusion (C-arm CTP) is a newly developed application that can provide cerebral perfusion images in the angio suite, similar to conventional multi-detector CTP in a diagnostic room. We introduce the workflow of C-arm CTP acquisition and our initial experience in a clinical setting.C-arm CTP was acquired with 40 ml of non-diluted contrast medium injected at 4 ml/s in the median cubital vein followed by 30 ml of saline injected at the same rate. The injection began 5 seconds after the acquisition was started. Two mask runs were followed with eight successive fill runs. Arterial input function was automatically calculated to deliver perfusion maps. Incidence of acquisition errors was evaluated in two phases.METHODC-arm CTP was acquired with 40 ml of non-diluted contrast medium injected at 4 ml/s in the median cubital vein followed by 30 ml of saline injected at the same rate. The injection began 5 seconds after the acquisition was started. Two mask runs were followed with eight successive fill runs. Arterial input function was automatically calculated to deliver perfusion maps. Incidence of acquisition errors was evaluated in two phases.C-arm CTP images were successfully acquired in all cases, and the images provided useful information under a stable examination protocol. However, we experienced some operational and systematic artifacts that degraded image quality of perfusion maps in Phase 1. The incident rate of errors was significantly improved in Phase 2.RESULTC-arm CTP images were successfully acquired in all cases, and the images provided useful information under a stable examination protocol. However, we experienced some operational and systematic artifacts that degraded image quality of perfusion maps in Phase 1. The incident rate of errors was significantly improved in Phase 2.C-arm CTP acquisitions were feasible during acute stroke treatment in the angio suite. It is expected that the image quality will be further improved through process improvement and reconstruction setting optimization to minimize unexpected artifacts in individual cases.CONCLUSIONC-arm CTP acquisitions were feasible during acute stroke treatment in the angio suite. It is expected that the image quality will be further improved through process improvement and reconstruction setting optimization to minimize unexpected artifacts in individual cases.